2010
DOI: 10.1111/j.1442-2042.2010.02628.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of idiopathic oligozoospermia: Comparison of mild, moderate and severe forms

Abstract: Objectives:To investigate the natural courses of mild , moderate and severe idiopathic oligozoospermia, and which factors or semen variables were of utmost importance in predicting the courses. Methods: A total of 208 men (age 29-47 years) who were diagnosed with mild , moderate and severe idiopathic oligozoospermia in a 9-year-period between January 2000 and December 2008 were followed up for more than 6 months. Results: Overall, 16 (24.6%) of 65 patients with severe oligozoospermia developed azoospermia, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…An analysis of the study patients in their fourth decade of life revealed that hormone imbalances may be closely related to the development of CPPS class IIIA and consequently, to poor semen quality. This result is in contrast to recent findings on the role of PRL, low levels of which have been shown to be associated with the metabolic syndrome and arteriogenic erectile dysfunction and with premature ejaculation, anxiety symptoms, and development of azoospermia in men with severe oligozoospermia (Corona et al, 2009; Bak et al, 2010). The LH levels were significantly different between our study patients and controls for reasons that remain enigmatic and warrant further studies.…”
Section: Discussioncontrasting
confidence: 99%
“…An analysis of the study patients in their fourth decade of life revealed that hormone imbalances may be closely related to the development of CPPS class IIIA and consequently, to poor semen quality. This result is in contrast to recent findings on the role of PRL, low levels of which have been shown to be associated with the metabolic syndrome and arteriogenic erectile dysfunction and with premature ejaculation, anxiety symptoms, and development of azoospermia in men with severe oligozoospermia (Corona et al, 2009; Bak et al, 2010). The LH levels were significantly different between our study patients and controls for reasons that remain enigmatic and warrant further studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In this regard, one study of 208 men with mild, moderate or severe idiopathic oligospermia concluded that those individuals with more severe oligospermia were more likely to progress to complete azoospermia, while those with mild or moderate oligospermia were more likely to remain stable or even improve over time (Won Bak et al 2010). However, the authors made no attempt to determine the cause of these patients' oligospermia and it was not clear how many, if any, were affected by testicular degeneration.…”
Section: Studying Testicular Ageing In the Stallionmentioning
confidence: 99%
“…20 Further, moderate to severe oligospermia has been shown to progress to azoospermia over time. 11 Therefore, patients with persistent moderate to severe oligospermia after treatment should consider banking their sperm if this was not completed prior to therapy. Medulloblastoma survivors who have received craniospinal irradiation and gonadotoxic chemotherapeutic agents, such as the subjects in our study, may have primary gonadal damage that is underdiagnosed due to follicle-stimulating hormone levels that appear to be "normal" or even low due to superimposed secondary hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Additionally, fertility counseling and sperm cryopreservation may help young adults cope with the cancer diagnosis 9 and decrease fears about having children. 10 Unfortunately, sperm banking has been strikingly underutilized, [11][12][13] largely due to inconsistent fertility counseling practices 8,[12][13][14][15] despite guidelines from the American Society of Clinical Oncology and the American Academy of Pediatrics. 16,17 Many barriers to providing adequate fertility counseling for pediatric cancer patients have been identified among practitioners, including urgency to start oncologic treatment, inadequate time and knowledge about preservation options, difficulty due to the sensitive nature of the topic, and lack of age-appropriate facilities for adolescent patients.…”
Section: Introductionmentioning
confidence: 99%